Inhibition of MSH6 augments the antineoplastic efficacy of cisplatin in non-small cell lung cancer as autophagy modulator - Varol, Ayşegül; Boulos, Joelle C.; Jin, Chunmei; Klauck, Sabine; Zhitkovich, Anatoly; Efferth, Thomas (Chemico-biological interactions, 2024)
The altered response to chemotherapeutic agents predominantly stems from heightened single-point mutations within coding regions and dysregulated expression levels of genes implicated in drug resistance mechanisms. The identification of biomarkers based on mutation profiles and expression levels is pivotal for elucidating the underlying mechanisms of altered drug responses and for refining combinatorial therapeutic strategies in the field of oncology. Utilizing comprehensive bioinformatic analyses, we investigated the impact of eight mismatch repair (MMR) genes on overall survival across 23 cancer types, encompassing more than 7500 tumors, by integrating their mutation profiles. Among these genes, MSH6 emerged as the most predictive biomarker, characterized by a pronounced mutation frequency and elevated expression levels, which correlated with poorer patient survival outcomes. The wet lab experiments disclosed the impact of MSH6 in mediating altered drug responses. Cytotoxic assays conducted revealed that the depletion of MSH6 in H460 non-small lung cancer cells augmented the efficacy of cisplatin, carboplatin, and gemcitabine. Pathway analyses further delineated the involvement of MSH6 as a modulator, influencing the delicate equilibrium between the pro-survival and pro-death functions of autophagy. Our study elucidates the intricate interplay between MSH6, autophagy, and cisplatin efficacy, highlighting MSH6 as a potential therapeutic target to overcome cisplatin resistance. By revealing the modulation of autophagy pathways by MSH6 inhibition, our findings offer insights into novel approaches for enhancing the efficacy of cisplatin-based cancer therapy through targeted interventions.